Emergency response and preparedness among Polish human milk banks: a comparison of the COVID-19 pandemic and the 2022 Ukrainian refugee crisis - Gawrońska, Małgorzata; Sinkiewicz-Darol, Elena; Wesołowska, Aleksandra (Frontiers in Nutrition, 2024)
In recent years Poland has faced two major emergencies: the COVID-19 pandemic, a global-scale public health emergency in 2020, and the outbreak of a full-scale war in Ukraine which made over 9 million Ukrainians -mostly women and children -to flee from their country through the Polish-Ukrainian border in 2022. In 2020 and 2022 we conducted two online questionnaires with human milk banks personnel to assess the impact of those emergencies on the human milk banking sector and its preparedness to face them. All 16 human milk bank entities operating in Poland were contacted and invited to participate in the study. For the first questionnaire distributed in 2020, we obtained a 100% response rate. For the second questionnaire, the response rate was 88% -14 out of 16 human milk banks completed the questionnaire. We compared those two emergencies in terms of to what extent the potential of the Polish human milk banks network was exploited in supporting vulnerable infants that were not breastfed. Our findings indicate that recommendations to provide donor human milk to infants separated from their mothers during COVID-19 pandemic were never fully implemented. Meanwhile, during the refugee crisis national legal provisions allowing equal access to public healthcare for Ukrainian citizens were rapidly implemented, enabling a more effective response from human milk banks to support vulnerable infants. However, no specific measures were introduced to support refugees outside of standard criteria of donor human milk provision. Our results highlight the limited response from the sector during emergencies, and underutilization of the potential of a nationwide network of professional human milk banks. Drawing on Polish experiences, we emphasize the importance of having procedures and legal provisions regarding human milk banking in place even in non-crisis settings, which would facilitate a rapid emergency response. We also emphasize the need to include implementation of emergency procedures in building a strong and resilient human milk banking system.